THE INFLUENCE OF BOPO LDR, AND LEVERAGE ON FINANCIAL PERFORMANCE (ROA) IN BANKING COMPANIES LISTED ON BURSA EFFECTS INDONESIA - Rizky Surya Andhayani Nasution (Institute of Computer Science (IOCS), 2021)
The bank is a financial institution whose function is to collect funds from the public. Commercial banks are also institutions that function to facilitate the flow of payment traffic. Every commercial bank must maintain the soundness of its bank to compete and provide full service to customers. The strength of the bank can be seen from the financial performance of the bank. Financial performance is one of the basic assessments of the company's financial condition that can be done based on an analysis of the company's financial ratios. The company's financial performance can be assessed through various variables. The financial performance of the banking sector, which is published through financial ratios, is grouped into liquidity ratios (LDR), solvency ratios (CAR and Leverage), operational efficiency (BOPO). The independent variables in this study are BOPO, LDR, and leverage. The dependent variable is financial performance. This study aims to examine the effect of Operational Efficiency (BOPO), Loan to Deposit Ratio (LDR), and Leverage on Return on Assets (ROA) as a proxy for Financial Performance. The research population is all banking companies listed in the Bursa Effect Indonesia (BEI). The research object was all banking companies listed in the Bursa Effect Indonesia (BEI) in 2010-2014. Sample selection was made by purposive sampling. The analytical method used in this study was to perform quantitative analysis, expressed by numbers calculated using statistical methods assisted by computer technology, namely SPSS 20. The data analysis method used in this study is the Multiple Linear Regression analysis method. In performing multiple linear regression analysis, this method requires testing the classical assumptions to get good regression results. The hypothesis testing uses the individual parameter significance test (t statistical) and the determinant coefficient test (R2). The results showed that the BOPO, LDR, and Leverage. Variables significant effect on ROA as well.